The Challenges of Ethical Review in Clinical Research of Traditional Chinese Medicine - Jie Zhang (Hindawi Limited, 2021)
The ethical review of TCM (traditional Chinese medicine) clinical research in China is highly consistent with that of Western medicine, but it lacks the characteristics and culture of TCM. Compared with modern medicine, TCM has its own characteristics, such as the theory of Yin-Yang and the five elements, the treatment of syndrome differentiation, and the compatibility of prescriptions. These characteristics determine the ethical particularity of TCM clinical research. This article discusses the challenges in the ethical review of TCM clinical research, such as scientific design, efficacy evaluation, risk assessment, informed consent, and placebo use. We propose opportunities and difficulties in the ethical review of TCM clinical research and provide some relevant suggestions.